International Entrepreneurship by African Firms: A Discussion on Constraints and Capabilities - Alo, Obinna; Ahmad, Arslan (My University, 2022)
This paper offers a conceptual assessment of some constraints associated with development of dynamic capabilities, for achieving a competitive advantage by African firms in international context. The paper advances the extant international entrepreneurship and dynamic capabilities literature by specifically highlighting the role of financial, managerial, institutional, and spiritual factors in relation to the development of capabilities needed for success in international markets. Several strategies including human resource management and human capital development practices which can potentially strengthen the dynamic capabilities linked to international entrepreneurial competitiveness of African firms are also suggested based on the conceptual discussion.
Keywords: Constraints and International Entrepreneurship; Capabilities; Business and Management not elsewhere classified